CULTURE AS CONTENT OF EDUCATION AND EDUCATIONAL DEMOCRACY - Sri Fani Dayanti; Firman; Riska Ahmad (Literasi Nusantara, 2021)
The educational paradigm in the future is democratic education and democratic education can only be realized in a democratic society, nation and state. Democracy, including education democracy, does not cure various developmental diseases, including getting quality education, but democracy provides the best opportunity for the implementation of justice and respect for human dignity. A democratic education will produce graduates who are able to participate in people's lives and are able to influence public policy decision making. Until now, democratic education is still an unrealized goal. However, in reality there are still educational phenomena that are not democratic, for example the phenomenon of the inadequate quality of educational processes and products